Exposure of human neurons to silver nanoparticles induces similar pattern of ABC transporters gene expression as differentiation: Study on proliferating and post-mitotic LUHMES cells. (April 2018) - Zuberek, M.; Stępkowski, T.M.; Kruszewski, M.; Grzelak, A.
Graphical abstract: Expression of ABC proteins after treating proliferating cells with silver nanoparticles and after differentiation process. Bold text represents upregulation and regular text represents downregulation. Highlights: Treatment of LUHMES cell line with silver nanoparticles results in similar pattern of changes in mRNA levels of ABC proteins as differentiation to mature neurones. Proliferating cells are far more susceptible to treatment with silver nanoparticles than differentiated neurons. Changes in ABC transporters expression are most probably induced by disturbances in cells redox balance, with particular emphasis on lipids oxidation. Abstract: The Lund human mesencephalic (LUHMES) cell line originated from mesencephalon of 8-week human foetus is a renowned in vitro model of human dopaminergic neurons. After differentiation the cells exhibit dopaminergic and neuronal characteristics of biochemically and morphologically mature dopamine-like neurons. In this study we analysed expression of 42 genes from ABC transporter superfamily in both proliferating cells and differentiated neurons after treatment with silver nanoparticles. ABC transporter superfamily is especially known due to the involvement in multidrug resistance phenomenon, but also involvement in transport through blood-brain barrier. Our results indicate that in neurons silver nanoparticles mainly attenuate transporters responsible for maintaining asymmetry of cellular membrane and homeostasis of lipids and cholesterol. Our results revealed also that proliferating foetal brain cells are by far more susceptible to silver nanoparticles than differentiated neurons.